Characterization and Heterologous Expression of UDP-Glucose 4-Epimerase From a Hericium erinaceus Mutant with High Polysaccharide Production - Zou, Gen; Ren, Juanbao; Wu, Di; Zhang, Henan; Gong, Ming; Li, Wen; Zhang, Jingsong; Yang, Yan (Frontiers in Bioengineering and Biotechnology, 2021)
Hericium erinaceus is an important medicinal fungus in traditional Chinese medicine because of its polysaccharides and other natural products. Compared terpenoids and polyketides, the analysis of synthetic pathway of polysaccharides is more difficult because of the many genes involved in central metabolism. In previous studies, A6180, encoding a putative UDP-glucose 4-epimerase (UGE) in an H. erinaceus mutant with high production of active polysaccharides, was significantly upregulated. Since there is no reliable genetic manipulation technology for H. erinaceus, we employed Escherichia coli and Saccharomyces cerevisiae to study the function and activity of A6180. The recombinant overexpression vector pET22b-A6180 was constructed for heterologous expression in E. coli. The enzymatic properties of the recombinant protein were investigated. It showed that the recombinant A6180 could strongly convert UDP-α-D-glucose into UDP-α-D-galactose under optimal conditions (pH 6.0, 30°C). In addition, when A6180 was introduced into S. cerevisiae BY4742, xylose was detected in the polysaccharide composition of the yeast transformant. This suggested that the protein coded by A6180 might be a multifunctional enzyme. The generated polysaccharides with a new composition of sugars showed enhanced macrophage activity in vitro. These results indicate that A6180 plays an important role in the structure and activity of polysaccharides. It is a promising strategy for producing polysaccharides with higher activity by introducing A6180 into polysaccharide-producing mushrooms.